Energy Saving Approach for Air Conditioner in Hotel Room - Mitwong, Hanphon; Kaewdee, Chatchai; Pansrinual, Weeraphol (Academic Journal of Industrial Technology Innovation, 2023)
The purpose of this research is to study the energy-saving approach for air conditioning in the hotel rooms. Industrial techniques such as quality tools and group discussions were applied to identify the problems and to determine the energy-saving solutions. The results showed that there were two solutions to save hotel energy consumption. The first method was to install an electronic device for checking the opening and closing of the door. The second method was to build the energy-saving awareness by using stickers. Both methods can reduce the problem of leaving the door open and low temperatures by 75%, while room electricity consumption was reduced by 17.63 percent.